Chapter Dante Alighieri nella lingua e nella cultura macedone - Gjurcinova, Anastasija (Biblioteca di Studi di Filologia Moderna, 2022)
The aim of this paper is to examine the influence of Dante Alighieri in the Macedonian cultural context through the translations and reception of his most important work, the Divina Commedia. The first part of the paper presents the translations of fragments of the poem published in the 1950s, translated by various Macedonian poets, and continues by presenting the translations by Georgi Stalev, who published parts of the poem in the 1960s, Inferno in 1967, and the whole poem (Inferno, Purgatorio and Paradiso) in 2006. The second part of the paper traces Dante's impact on the literary works of Georgi Stalev, Bogomil Ǵuzel and Blaže Koneski as well as the poet's influence in other domains of Macedonian culture.